Konsep Pendidikan Keluarga Dalam Perspektif Al-Qur'an Kajian (Q.S.Thaaha Ayat 132) - Putri, Nabila Irfany; Razzaq, Abdur; Imron, Kristina (LPPM Institut Pendidikan Nusantara Global, 2024)
This research discusses the concept of family education in the Qur'anic perspective, particularly through the study of Surah Thaaha verse 132. This verse emphasizes the importance of educating the family, especially in the spiritual aspect, focusing on the obligation to establish prayer and maintain a good relationship with Allah. In this verse, there is an order to encourage family members to pray consistently and patiently. Family education in this perspective is not only an individual responsibility, but involves all family members to jointly uphold religious values. This research uses thematic interpretation method to explore the educational values in the verse, as well as how it is applied in Muslim family life. It is found that education in the family should be holistic, covering spiritual, moral, and social aspects, with the main goal of forming a strong character in faith and obedience to Allah.